The nature of US and EU foreign trade relations with reference to TTIP - Strenja, Rajko; Lukavac, Marko (Oeconomica Jadertina, 2018)
The US and European Union interdependence at the economic, political and security level historically represented the source of co-operation, but also tensions between two globally important economies. The strong economic, political and security ties between the United States and the EU enabled these economies to gain global supremacy, because of the links between the most powerful according to the criteria of economics and education. With the objective of keeping global supremacy, the US and the EU have strived to agree on contemporary high-standard bilateral trade agreement, socalled TTIP. The aim of the Transatlantic Trade and Investment Partnership Agreement is to reach an agreement on further liberalization and increase of market approach through elimination of obstacles in trade of goods, services, agricultural products and investments, as well as in procedures related to public procurement. The important objectives of the agreement are also the increase of regulatory compliance and cooperation in the area of foreign trade and security policy, investment and development of new rules associated with direct foreign investments, rights arising from intellectual property, labor rights and environmental standards. This article will highlight the most important disagreements between the US and the EU associated with so-called "TTIP" with primary purpose of defining potential risks for sustainable growth of the EU economy in the future.
Keywords: US; EU; protectionism; free trade; WTO; TTIP